2015
DOI: 10.1007/s00704-015-1693-6
|View full text |Cite
|
Sign up to set email alerts
|

Recent warming trend in the coastal region of Qatar

Abstract: The objective of this study was to analyze longterm temperature-related phenomena in the eastern portion of the Middle East, focusing on the coastal region of Qatar. Extreme temperature indices were examined, which were defined by the Expert Team on Climate Change Detection and Indices, for Doha, Qatar; these indices were then compared with those from neighboring countries. The trends were calculated for a 30-year period , using hourly data obtained from the National Climatic Data Center. The results showed sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 52 publications
6
14
0
Order By: Relevance
“…The Sen's slope estimates that mean temperature has increased by 1.02 ℃ over the last 30 years with 0.034℃ per year increment. These warming trends are in agreement with the previous studies in Qatar 29 , Saudi Arabia 1987 1988 1989 1990 1991 1992 1993 1994 1995 1996 1997 1998 1999 2000 2001 2002 2003 2004 2005 2006 2007 2008 2009 2010 2011 2012 2013 2014 2015…”
Section: Mann-whitney-pettitt Change Point Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…The Sen's slope estimates that mean temperature has increased by 1.02 ℃ over the last 30 years with 0.034℃ per year increment. These warming trends are in agreement with the previous studies in Qatar 29 , Saudi Arabia 1987 1988 1989 1990 1991 1992 1993 1994 1995 1996 1997 1998 1999 2000 2001 2002 2003 2004 2005 2006 2007 2008 2009 2010 2011 2012 2013 2014 2015…”
Section: Mann-whitney-pettitt Change Point Analysissupporting
confidence: 92%
“…The purpose of this study is to investigate spatial and temporal variability in precipitation and temperature for annual and seasonal timescales and highlight the extent to which these climatic changes may affect the EWF nexus in the state of Qatar. In addition, this study is expected to increase the knowledge regarding the annual and seasonal distribution of temperature and precipitation and to fill the gap of the previous research as described above, where 29 analysed data from one weather station. This study aims to increase the representation of Qatar's climate by using climatic data from six weather stations over a 30 year period.…”
Section: Introductionmentioning
confidence: 99%
“…Literature analyzing vulnerability and risk scenarios for these infrastructure is lacking despite evidence of tangible effects of global warming. Cheng et al [91] indicated a trend of spatially consistent warming trends in Qatar and the region. Farahat [92] studied air pollution in the GCC including greenhouse gases.…”
Section: Climate Changementioning
confidence: 98%
“…The temperature of this arid climate region varies seasonally from 11 to 15°C in the winter to 34-40°C in the summer (Rezai et al, 2004). The mean daily temperature in summer is commonly 30-35°C (temperature can exceed 50°C), whereas the mean annual temperature is only 25°C (Cheng et al, 2017). Therefore, as a result of high temperature and intense evaporation, the surface salinity can reach upto 58 psu in shallow region, especially in summer (Beltagy, 1983).…”
Section: Study Areamentioning
confidence: 99%